NF1 Mutations Are Common in Desmoplastic Melanoma. (October 2015) - Wiesner, Thomas; Kiuru, Maija; Scott, Sasinya N.; Arcila, Maria; Halpern, Allan C.; Hollmann, Travis; Berger, Michael F.; Busam, Klaus J.
Abstract : Desmoplastic melanoma (DM) is a rare variant of melanoma with distinct clinical, histopathologic, and immunohistochemical features. Clinically, DM differs from conventional melanoma by a higher propensity for local recurrence and less frequent metastatic spread to regional lymph nodes. In its pure form, DM has a distinct appearance displaying a low density of fusiform melanocytes in a collagen-rich matrix. Whereas a number of mutations have been identified in primary melanoma, including BRAF, NRAS, GNAQ, GNA11, and KIT, and the occurrence of these mutations has been found to correlate to some extent with the histopathologic features, anatomic site, and/or mode of sun exposure, no distinct set of mutations has so far been reported for DM. To study the potential association of neurofibromin ( NF1 ) mutations with DM, we examined 15 desmoplastic and 20 non-DMs by next-generation sequencing. Mutations of the NF1 gene were found in 14 of 15 (93%) DMs and 4 of 20 (20%) non-DMs. The high frequency of NF1 mutations in DMs suggests an important role for NF1 in the biology of this type of melanoma.